'Nomad Villages' in north‐eastern Jordan: from Roman Arabia to Umayyad Urdunn. (May 2014) - Kennedy, David L.
<x xml:space="preserve">Abstract</x> The traces of dispersed houses in desert or steppic regions of northern Jordan and southern Syria have been augmented by recent discoveries and fieldwork. The evidence suggests that they are dated to the Umayyad period, although often with traces of Late Roman/Jafnid (Ghassanid) origins. The new discoveries allow an enrichment of our knowledge for the period and provide a contrast with the better known Desert Castles and Qusur that dominate the evidence for this period.